UPACARA NGUSABA BUKAKAK : KONTESTASI MASYARAKAT DAN DAYA TARIK WISATA - Sudika I Wayan (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The cultural manifestations carried out jointly, especially by Hindus in Bali, are demonstrated through this local wisdom to express gratitude to God or Ida Sang Hyang Widhi Wasa. Titib (2007: 41) states that local wisdom gives a hue and coloring the life of Hinduism and Balinese culture. Hinduism gives enlightenment to Balinese people while still preserving existing beliefs and traditions. Every region in Bali has its own religious tradition that is characteristic of one of them in the village of Giri Mas, which is an ancient ceremony that takes place from generation to generation namely the Ngusaba Bukakak Ceremony conducted by the community in Giri Emas Village. Subak is a Balinese cultural heritage in the form of an irrigation system that regulates the distribution of water management based on patterns of harmony and togetherness based on formal rules and religious values. The management of conventional irrigation systems tends to only be based on the concepts of efficiency based on formal rules, with an economic mindset. Meanwhile, the concepts of effectiveness, religious values, and management of irrigation systems based on harmony and togetherness, are well-organized and flexible in this subak system in Bali. The background of the establishment of this organization was several thousand years ago because of the steep topography and conditions of the rivers in Bali. This causes the water source in a farmer's rice complex is generally quite far and limited. To be able to channel water to a rice field complex, they must make a tunnel through the rocky hills. This condition caused the Balinese farmers to gather themselves and form a Subak organization. Keyword : Ngusaba Bukakak, Community Contestation, Tourist Attraction